Combination of Psoriasis and Vitiligo in a Child with Sotos Syndrome: Clinical Case - Elena N. Efanova; Daria G. Taskaeva ("Paediatrician" Publishers LLC, 2024)
Background. Psoriasis and vitiligo are chronic, relatively common dermatological diseases. Meanwhile, their combination in children is rare. The combination of psoriasis and vitiligo in a child with Sotos syndrome has not been previously described. Clinical case description. The boy, 10 years old, was hospitalized with complaints (according to his mother) of rashes on the scalp, body, and limbs, with mild itching that was not related to the time of day. The pathological skin process was widespread. The patient was hyperactive, restless, emotionally labile, irritable. Complaints of rashes was mentioned firstly at the age of 7. Sotos syndrome was established at the age of 8 (variant c.6559C>T (p.Arg2187Ter) in 23 exon of the NSD1 gene (5q35.3), autosomal dominant type of inheritance (pathological allele de novo)). Psoriasis vulgaris was diagnosed with secondary vitiligo (localized form) at the age of 8.5 years. Symptomatic antipruritic and external pathogenetic therapy was performed in the hospital. Phototherapy was not prescribed due to the relative contradiction (small retrocerebral cyst) and the peculiarities of major disease (hyperactivity, restlessness) that complicated to place the child in the phototherapy booth. Positive dynamics was noted during the treatment (14 days): no itching, decrease of peeling severity, flattening and blanching of psoriatic rash elements to spots of post-inflammatory hypopigmentation. The lesion (focus of depigmentation) on the right knee joint skin remained unchanged. The patient was discharged to outpatient care. The prognosis for Sotos syndrome and skin lesions is favorable. Conclusion. The first medical observation of the child with Sotos syndrome burdened with psoriasis and vitiligo is presented. The pathogenetic correlation of these diseases is not clearly defined. Management of such cases requires the joint collaboration of dermatologists, geneticists and pediatricians.